56.5k views
4 votes
Simplify the expression and enter your answer below.(151/5,5Answer here

User Kazz
by
5.0k points

1 Answer

5 votes

First, let's look at the power rule of exponents, below:


(a^b)^c=a^(bc)

This means when a power is raised to another power, we mutliply the exponents. Applying this rule to our problem and simplifying:


\begin{gathered} (a^b)^c=a^(bc) \\ (15^{(1)/(5)})^5 \\ =15^{(1)/(5)*5} \\ =15^{(5)/(5)} \\ =15^1 \\ =15 \end{gathered}

The simplified answer is "15"

Answer15
User Jiby
by
5.2k points